2012
DOI: 10.1371/journal.pone.0038838
|View full text |Cite
|
Sign up to set email alerts
|

The Centrosomal Kinase Plk1 Localizes to the Transition Zone of Primary Cilia and Induces Phosphorylation of Nephrocystin-1

Abstract: Polo-like kinase (Plk1) plays a central role in regulating the cell cycle. Plk1-mediated phosphorylation is essential for centrosome maturation, and for numerous mitotic events. Although Plk1 localizes to multiple subcellular sites, a major site of action is the centrosomes, which supports mitotic functions in control of bipolar spindle formation. In G0 or G1 untransformed cells, the centriolar core of the centrosome differentiates into the basal body of the primary cilium. Primary cilia are antenna-like senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 55 publications
1
46
0
Order By: Relevance
“…Previous work suggests that PCM1 is important in the formation of primary cilia by associating with CEP290 and BBSome during the ciliogenesis (Kim et al, 2008;Nachury et al, 2007), indicating that PCM1 may play dual role in regulating primary cilia dynamics: When cells exit cell cycle and enter quiescence, PCM1 maintains steady state for primary cilia assembly independent of Plk1; whereas in proliferating cells, PCM1 is needed to recruit Plk1 to induce ciliary resorption before mitotic entry. During the preparation of this manuscript, two reports were published online and showed that the kinase activity of Plk1 is required for primary cilia disassembly (Lee et al, 2012;Seeger-Nukpezah et al, 2012). Lee and co-workers showed that Plk1 interacts with Dishevelled 2 (Dvl2) and promotes cilia disassembly; and Schermer and co-workers showed that Plk1 induces the phosphorylation of nephrocystin-1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work suggests that PCM1 is important in the formation of primary cilia by associating with CEP290 and BBSome during the ciliogenesis (Kim et al, 2008;Nachury et al, 2007), indicating that PCM1 may play dual role in regulating primary cilia dynamics: When cells exit cell cycle and enter quiescence, PCM1 maintains steady state for primary cilia assembly independent of Plk1; whereas in proliferating cells, PCM1 is needed to recruit Plk1 to induce ciliary resorption before mitotic entry. During the preparation of this manuscript, two reports were published online and showed that the kinase activity of Plk1 is required for primary cilia disassembly (Lee et al, 2012;Seeger-Nukpezah et al, 2012). Lee and co-workers showed that Plk1 interacts with Dishevelled 2 (Dvl2) and promotes cilia disassembly; and Schermer and co-workers showed that Plk1 induces the phosphorylation of nephrocystin-1.…”
Section: Discussionmentioning
confidence: 99%
“…By these means, primary cilia control cellular processes during development and in the adult organism. 20,[27][28][29][30][31][32][33][34][35][36] In addition, specialized non-motile sensory cilia are present on neurons in the olfactory epithelium of the nasal Table 1. Common types of congenital heart defects Congenital heart defect Abbreviation Characteristics…”
Section: Cilia Ciliopathies and Chd-an Overviewmentioning
confidence: 99%
“…The AURKA-activating interaction with NEDD9 is stimulated by the binding of Ca 2+ -liganded calmodulin to AURKA [15,16]. AURKA-NEDD9 interactions are also stabilized by an interacting PLK1-DVL2 complex at the basal body [11] and the adjacent ciliary transition zone [17]; in the normal initiation of ciliogenesis after mitosis, BUBR1 restrains DVL2 expression [18]. …”
Section: Specific Signaling Pathways In Carcinogenesis With Ciliarmentioning
confidence: 99%